1994
DOI: 10.1128/iai.62.7.2849-2856.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a Cryptococcus neoformans gene, GPA1, encoding a G-protein alpha-subunit homolog

Abstract: We have isolated a gene, GPA1, from Cryptococcus neoformans by the PCR technique. DNA sequencing of the GPA1 clone suggested that it encodes a protein homologous to the G-protein alpha-subunit family. Comparison of the deduced amino acid sequence of the GPA1-encoded protein revealed that it is about 45% identical to several mammalian Gi alpha subunits and 48% identical to the G alpha protein Gpa2 from Saccharomyces cerevisiae. G alpha proteins are known to be involved in mating of other yeasts, such as S. cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Both the MAP kinase and cAMP signaling cascades regulate mating and pathogenicity of C. neoformans ( [115,116], reviewed in [117,118]). The C. neoformans GK subunit Gpa1 was found to be homologous in sequence to the S. cerevisiae GK protein Gpa2 involved in nutrient sensing during pseudohyphal di¡erentiation [10,28,119]. Gpa1 plays a key role in cAMP signaling and virulence [115].…”
Section: Mating and Virulence In C Neoformansmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the MAP kinase and cAMP signaling cascades regulate mating and pathogenicity of C. neoformans ( [115,116], reviewed in [117,118]). The C. neoformans GK subunit Gpa1 was found to be homologous in sequence to the S. cerevisiae GK protein Gpa2 involved in nutrient sensing during pseudohyphal di¡erentiation [10,28,119]. Gpa1 plays a key role in cAMP signaling and virulence [115].…”
Section: Mating and Virulence In C Neoformansmentioning
confidence: 99%
“…As with gpa3, uac1, and adr1 mutants of U. maydis, a ¢l1 mutant of its close relative Ustilago hordei, is also constitutively ¢lamentous and is restored to budding growth by exogenous cAMP [147,148]. Fil1 shares a high degree of sequence identity to the GK subunit Gpa1 from the basidiomycete C. neoformans, required for virulence of this human pathogen [115,119]. Like cAMP, overexpression of FIL1 also suppressed the ¢lamentous growth of starved haploid wild-type strains, suggesting that Fil1 functions to activate adenylyl cyclase [148].…”
Section: Dimorphic Transition and Pathogenicity In U Maydismentioning
confidence: 99%
“…Preliminary molecular studies of mating in C. neoformans have identified a number of genes bearing substantial sequence similarity to S. cerevisiae mating-associated genes. These genes include homologues of GPA1 (Tolkacheva et al, 1994;Alspaugh et al, 1997), STE12 (Wickes et al, 1997), STE4 (Wang et al, 2000) and a pheromone (Moore and Edman, 1993). Various genetic and molecular manipulations of these genes have demonstrated that at least some of their functions are conserved.…”
Section: Introductionmentioning
confidence: 99%
“…Because some studies have indicated direct interaction of ScGpa1p with the mating-specific MAPK Ste50p (Metodiev et al, 2002) and direct coupling of the activated Ga subunit with Scp160 (an RNA-binding protein) (Guo et al, 2003), a positive role of ScGpa1p in mating cannot be discarded. Ga subunits playing positive roles in mating have been described in other fungal species, for example Gpa1p (homologous to ScGpa2p, which is involved in cAMP regulation) in the basidiomycete Cryptococcus neoformans (Tolkacheva et al, 1994;Alspaugh et al, 1997), Gpa3p in Ustilago maydis (Regenfelder et al, 1996), and Gpa1p in the fission yeast Schizosaccharomyces pombe (Obara et al, 1991). In addition to the pheromone response pathway, in K. lactis a cAMP-nutrient-sensing signalling pathway regulated by a Ga2 (KlGpa2p) subunit has been identified (Saviñón-Tejeda et al, 1996), which is unrelated to the mating pathway.…”
Section: The G Proteinmentioning
confidence: 99%